Phanerozoic continental growth and gold metallogeny of Asia - Goldfarb R.J.; Taylor R.D.; Collins G.S.; Goryachev N.A.; Orlandini O.F. (My University, 2014)
The Asian continent formed during the past 800. m.y. during late Neoproterozoic through Jurassic closure of the Tethyan ocean basins, followed by late Mesozoic circum-Pacific and Cenozoic Himalayan orogenies. The oldest gold deposits in Asia reflect accretionary events along the margins of the Siberia, Kazakhstan, North China, Tarim-Karakum, South China, and Indochina Precambrian blocks while they were isolated within the Paleotethys and surrounding Panthalassa Oceans. Orogenic gold deposits are associated with large-scale, terrane-bounding fault systems and broad areas of deformation that existed along many of the active margins of the Precambrian blocks. Deposits typically formed during regional transpressional to transtensional events immediately after to as much as 100. m.y. subsequent to the onset of accretion or collision. Major orogenic gold provinces associated with this growth of the Asian continental mass include: (1) the ca. 750. Ma Yenisei Ridge, ca. 500. Ma East Sayan, and ca. 450-350. Ma Patom provinces along the southern margins of the Siberia craton; (2) the 450. Ma Charsk belt of north-central Kazakhstan; (3) the 310-280. Ma Kalba belt of NE Kazakhstan, extending into adjacent NW Xinjiang, along the Siberia-Kazakhstan suture; (4) the ca. 300-280. Ma deposits within the Central Asian southern and middle Tien Shan (e.g., Kumtor, Zarmitan, Muruntau), marking the closure of the Turkestan Ocean between Kazakhstan and the Tarim-Karakum block; (5) the ca. 190-125. Ma Transbaikal deposits along the site of Permian to Late Jurassic diachronous closure of the Mongol-Okhotsk Ocean between Siberia and Mongolia/North China; (6) the probable Late Silurian-Early Devonian Jiagnan belt formed along the margin of Gondwana at the site of collision between the Yangtze and Cathaysia blocks; (7) Triassic deposits of the Paleozoic Qilian Shan and West Qinling orogens along the SW margin of the North China block developed during collision of South China; and (8) Jurassic(?) ores on the margins of the Subumusu block in Myanmar and Malaysia. Circum-Pacific tectonism led to major orogenic gold province formation along the length of the eastern side of Asia between ca. 135 and 120. Ma, although such deposits are slightly older in South Korea and slightly younger in the Amur region of the Russian Southeast. Deformation related to collision of the Kolyma-Omolon microcontinent with the Pacific margin of the Siberia craton led to formation of 136-125. Ma ores of the Yana-Kolyma belt (Natalka, Sarylakh) and 125-119. Ma ores of the South Verkhoyansk synclinorium (Nezhdaninskoe). Giant ca. 125. Ma gold provinces developed in the Late Archean uplifted basement of the decratonized North China block, within its NE edge and into adjacent North Korea, in the Jiaodong Peninsula, and in the Qinling Mountains. The oldest gold-bearing magmatic-hydrothermal deposits of Asia include the ca. 485. Ma Duobaoshan porphyry within a part of the Tuva-Mongol arc, ca. 355. Ma low-sulfidation epithermal deposits (Kubaka) of the Omolon terrane accreted to eastern Russia, and porphyries (Bozshakol, Taldy Bulak) within Ordovican to Early Devonian oceanic arcs formed off the Kazakhstan microcontinent. The Late Devonian to Carboniferous was marked by widespread gold-rich porphyry development along the margins of the closing Ob-Zaisan, Junggar-Balkhash, and Turkestan basins (Amalyk, Oyu Tolgoi); most were formed in continental arcs, although the giant Oyu Tolgoi porphyry was part of a near-shore oceanic arc. Permian subduction-related deformation along the east side of the Indochina block led to ca. 300. Ma gold-bearing skarn and disseminated gold ore formation in the Truong Son fold belt of Laos, and along the west side to ca. 250. Ma gold-bearing skarns and epithermal deposits in the Loei fold belt of Laos and Thailand. In the Mesozoic Transbaikal region, extension along the basin margins subsequent to Mongol-Okhotsk closure was associated with ca. 150-125. Ma formation.
Keywords: Carlin-type; asia; gold; tectonics; orogenic gold; epitermal; porphyry